2018
DOI: 10.1039/c8ra02511h
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethylated proline analogues as efficient tools to enhance the hydrophobicity and to promote passive diffusion transport of the l-prolyl-l-leucyl glycinamide (PLG) tripeptide

Abstract: The incorporation of trifluoromethylated proline analogues in the tripeptide PLG enhances its hydrophobicity and promotes passive diffusion transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…The hydrophobicity of amino acid analogues is an important consideration when designing peptide sequences, and some trifluoromethylated ProAs have recently been applied in attempts to improve the membrane permeability of therapeutic peptide constructs. 87 We have demonstrated that the local polarity differences introduced by the incorporation of 4-methyl-and 4-fluoroprolines impact structural stability at a level nearly equal to the preorganization from the inter-carbonyl alignment. 88 A notable fact is that 4-methylprolines are abundant in natural products, 89,90 and these are the simplest alkylproline derivatives among others occurring in nature.…”
Section: Lipophilicitymentioning
confidence: 90%
See 1 more Smart Citation
“…The hydrophobicity of amino acid analogues is an important consideration when designing peptide sequences, and some trifluoromethylated ProAs have recently been applied in attempts to improve the membrane permeability of therapeutic peptide constructs. 87 We have demonstrated that the local polarity differences introduced by the incorporation of 4-methyl-and 4-fluoroprolines impact structural stability at a level nearly equal to the preorganization from the inter-carbonyl alignment. 88 A notable fact is that 4-methylprolines are abundant in natural products, 89,90 and these are the simplest alkylproline derivatives among others occurring in nature.…”
Section: Lipophilicitymentioning
confidence: 90%
“…Our data will enable researchers to rationally and more accurately predict and plan experiments that involve Pro substitutions, in applications such as in the design of peptidyl-prolyl cis-trans isomerase inhibitors, [72][73][74][75][76] expansion of the genetic amino acid repertoire [13][14][15] as well as in protein engineering [21][22][23][24][25][26] and development of other peptide therapeutics. 87 However, the most outstanding application is the use of fluorine-labelled ProAs in 19 F NMR studies of polypeptides. A few works have suggested the use of fluoroprolines for this purpose (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1), can solve this problem while simultaneously enhancing other properties of interest. 3,[16][17][18][19] Even fluorinating only a few residues may enhance the hydrophobicity and passive diffusion of peptides through membranes, 20 the proteolytic resistance 21 and anti-microbial activity of proteins, 22 in addition to tuning their thermal stability, 23 making this synthetic approach of wide interest. [24][25][26][27][28] Still, a caveat of using fluorination to control protein properties remains: do we understand the factors influencing the hydrophobic effect involving fluorinated amino acids?…”
Section: Introductionmentioning
confidence: 99%
“…The internalization of CPPs starts through electrostatic interactions between positively charged amino acids and negatively charged moieties on the cellular surface (19,48). Despite the fact that endocytosis and direct translocation can simultaneously occur, highly hydrophobic peptides easily interact with the plasma membrane before being taken up by cells (49,50). Accordingly, our results showed that the peptides' performance, in terms of GAGs affinity and membrane penetration, increased with increasing hydrophobicity.…”
Section: Discussionmentioning
confidence: 68%